We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
217
3
avatar+107 

a.Determine the missing side length:

 

 [asy] size(4cm);void mra(pair u, pair v, pair w, real r){ draw(v+(u-v)/length(u-v)*r--v+(u-v)/length(u-v)*r+(w-v)/length(w-v)*r--v+(w-v)/length(w-v)*r);} pair a=(0,0); pair b=(28,0); pair c=(0,-21);draw(a--b--c--a);mra(c,a,b,2.5);label(

 

b. Determine the missing side length

 

 

[asy] size(4cm);void mra(pair u, pair v, pair w, real r){ draw(v+(u-v)/length(u-v)*r--v+(u-v)/length(u-v)*r+(w-v)/length(w-v)*r--v+(w-v)/length(w-v)*r);} pair a=(0,42/sqrt(85)); pair b=(-36/sqrt(85),0); pair c=(49/sqrt(85),0);draw(a--b--c--a);mra(c,a,b,0.75);label(

 

 

c. Determine the missing side length

[asy] size(4cm);void mra(pair u, pair v, pair w, real r){ draw(v+(u-v)/length(u-v)*r--v+(u-v)/length(u-v)*r+(w-v)/length(w-v)*r--v+(w-v)/length(w-v)*r);} pair k=(0,0); pair l=(3,sqrt(3)); pair n=(3,0);label(rotate(30)*

 Mar 28, 2019
 #1
avatar+4299 
+4

1. 28^2+21^2=c^2,\(c=35.\)

2. 6^2+7^2=c^2, c^2=85, \(c=\sqrt{85}.\)

3. \(c^2+(\sqrt{3})^2=(2\sqrt{3})^2, c^2=9, c=3.\)

.
 Mar 28, 2019
 #2
avatar+1354 
+3

Ok, all of these are relativaly simple.

The formula you will be working with for all of these is a^2+b^2=c^2

Im not going to give you the answers only explain how to do it.

#1. 28 and 21 are a and b. Insert them into the formula to get 28^2+21^2=c^2

Solve for 28^2+21^2 and get 1225

now you are at 1225=c^2

Your answer will be the square root of 1225.

#2. In this problem 6 and 7 are a and b.

Put them in the equation above to get 36+49=c^2

Your answer for this will be the square root of 85

#3. In this problem 2 times the square root of 3 is c and the square root of 3 is a.

Put them into the equation above to get the square root of 3 squared (3) + b^2=2times the square root of 3 squared (2 times the square root of 3.

This gets us to the Square root of 3+ b^2=2 times the square root of 3

Minus Square root of 3 from right side to get b^2 equals the square root of three. so b equals the square root of the square root of three

Have A nice day!

 Mar 28, 2019
 #3
avatar+107 
0

Thanks!

SoulSlayer615  Mar 30, 2019

9 Online Users